Efek Antihiperglikemi Kacang Panjang (Vigna Unguiculata) - Ian Ivantirta (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Diabetes is a chronic disease that occurs when the pancreas cannot produce enough insulin, or when the body cannot use insulin that is produced effectively. Diabetes cannot be cured but can be controlled by using drugs. Because the number of diabetics in Indonesia is quite high, alternative treatments are needed for diabetics. Long beans can be used as anti-hyperglycemia because they contain high fiber, flavonoids, saponins and flavonols. Where flavonoids are anti-oxidants that can reduce free radicals in pancreatic β cells by capturing free radicals that exist in cells. So long beans can be used as herbal ingredients that can reduce blood glucose levels in diabetics